APPLICATION OF CRISPR TO INCREASE MEAT YIELD IN CHICKEN - RAUF, U; BATOOL, F; NOOR, YA; USMAN, M; SHAH, KA; IMRAN, M; AHMAD, M; QOUSAIN, SMZ; KAZMI, SUEF; ZAMAN, H (Biological and Clinical Sciences Research Journal, 2024)
Meat production is one of the major purposes of the poultry industry. Meat is full of protein and accomplishes the protein requirement of the diet. This study was carried out to attempt to use CRISPR-mediated genome editing of chicken to increase meat yield. For this purpose, CRISPR was used to edit the gene sequence and then it was allowed to infect the PGC’s (Primordial germ cells). The successfully edited PGC’s having blocked exon 3 of MSTN gene were then injected into the blood bloodstream of 2.6 days of fertilized egg cells. The eggs were incubated up to hatch. The wild type was taken as control and the Mutated ones as T1. The CRD was used with three replications to find the significance of variation in To and T1. The weight of chicks for T0 (wild type) and T1 (Mutated) was significantly different. The average weight of three replications of each treatment was compared through a bar graph. it was found that the CRISPR-mediated edited chicks were more weighted than that of their wild types. The CRISP-mediated inhibition of MSTN has a significant effect on muscle growth in chickens. The more such genes may be targeted to get more meat yield.